The effectiveness of guided question technique to improve student' ability in writing descriptive text in the seventh grade of SMPN 1 Pabelan - Mustaidah, Mustaidah; Umami, Mashlihatul; Ruwandi, Ruwandi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The objectives of the study were to find out the effectiveness of using the guided questions technique to improve students’ ability in writing descriptive text and the profile of students’ ability to write descriptive text before and after using the guided question technique the seventh grade of SMPN 1 Pabelan in the academic year 2023/2024. The researcher utilized a true experimental research method for this research. This research used a random sampling technique to obtain a sample. In seventh grade, there are 6 parallel classes, each class takes 5 students as samples. So, they were collected into one class as a control class and an experimental class. A test was employed as the means for gathering the data. The students' descriptive writing skills were assessed before treatment using a pretest. Following the treatment, their abilities were measured again using a post-test. Statistical analysis was conducted on the collected data from the test. The result showed the differences in students’ writing ability before and after using the guided question technique. The student's lowest pretest result was 30. After using the guided question technique, the student's post-test result showed the number 80. Meanwhile, after taking part in the lesson using the guided question technique, the lowest post-test result was 80, the highest post-test result was 95. This shows that the use of the guided question technique is effective in improving students' ability to write. The data analysis revealed that the research hypothesis was confirmed as the T –Test value of ±25.154 was greater than the T – Table value of 2.045. The table has 29 degrees of freedom (df). This means that using guided questions techniques is effective enough to improve students’ writing skill.